Restricting environmental damage resulting from economic activities: a Polanyian analysis. (1st September 2021) - Senker, Peter
Abstract : Economic activities continue to cause considerable environmental damage. The extent of damage could be such that the environment in and around our planet will be affected, making survival difficult for human beings, for other animals, and for plants and insects. The paper reviews economic developments from the nineteenth century and how these have been influenced by orthodox economic theories. Markets are central to orthodox economics, and to policies which have been implemented recently to restrict global warming. Since the 1980s, policies based on orthodox economics and neoliberalism have been widely implemented by governments, and also by international organizations. Such policies are evaluated and found to be seriously inadequate. Studies of environmental implications of the development of two major sectors of the world economy follow. Policies which are concerned only to restrain climate change are unlikely to be adequate by themselves. Policies which take a holistic approach to considering all the important impacts of human economic activity on the environment have greater prospects of success. The paper concludes by suggesting research and analysis be undertaken urgently to assist with the design and implementation of more effective policies to reduce the damage to the environment caused by human economic activities.